Drip, drop - Weeks, Sarah; Manning, Jane, 1960- (New York : HarperCollins, 2000)
Pip Squeak the mouse is kept awake all night by the drips from his leaky roof.
G1
Keywords: Mice -- Fiction; Rain and rainfall -- Fiction; Stories in rhyme